Investigating the lived experience of adolescents with a history of self-mutilation - Asgharzadeh, Ali; Mohammadpanah Ardakan, Azra; Aryanpour, Hamid Reza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The ups and downs of puberty are the passage from childhood to adulthood and are sometimes associated with contradictions and aggression. Self-harm can be mentioned as one of the abnormal behaviors of this period; And because of its harmful nature, it’s important to study in this area. Self-mutilation can be defined as intentional injury to the body without the purpose of suicide. In general, the present study sought to examine the lived experience of adolescents with a history of self-harm, It was done in detail with the aim of examining the emotional, cognitive, psychological experiences, physical injuries and family factors affecting adolescents’ self-mutilation.The study population included all adolescents aged 12-18 years in Kerman who had attempted suicide in 2021. Methods: The sampling method was purpose-based. And the criterion for entering the sample was to have at least one history of self-harm. This research has studied the lived experience of adolescents with a history of self-harm with a phenomenological method and a thematic approach, and the research data have been analyzed using a descriptive (Klaizi) phenomenological method. Results: After conducting ten interviews, the research was saturated and 49 primary concept codes were extracted, which represented the lived experience of adolescents with a history of self-harm; Then, similar and close concepts were placed in 15 major classes and 5 main categories,which are: 1- Individual characteristics (extraversion, Neuroticism, openness to experience) 2- Effective family factors (family, living environment) 3- maturity-related characteristics (cognitive characteristics, emotional characteristics) 4- Clinical disorders (behavior, mood disorders, intermittent explosive disorders, anxiety disorders and clinical pattern of personality) 5- Emotions related to self-harm (feeling before committing suicide, feeling after committing suicide). Conclusion: self-harming behavior has different functions for each person and recognizing these functions can help therapists in diagnosing treatment and how to deal with people with the disease. Some of these functions are: emotion regulation, Escape from suicide, Draw attention, ask grith, show courage, escape from routine life